Information Value and Interregional Input-Output Structure - Toshiaki Takita (International Telecommunications Society (ITS), 2017)
This paper establishes an economic theory of information value and volume that differs from Shannon's mathematical theory of communication (Shannon, 1948). The economics of information should be recognized as an important frontier field of economics to explore the 4th industrial revolution including Internet of the things (IoT) and artificial intelligence (AI). However, we need to construct an fundamental way to analyse information flow and stock. Because of this, the value of information goods as a non-market or market good is measured as agents' willingness to pay (WTP) for travel and telecommunication from the overall viewpoint of transportation and telecommunication economics. And we construct an economic model for analysing the information flow between head and branch offices. This firms' total profit is maximized by optimally imputing the amount of time which employees devote to collecting and processing internal and external information. Here, factors of production are internal and external information flows and stock information. Finally we propose information inputoutput table explaining inter-regional information flow of the sample economic model.
Keywords: D21; J29; L63; R15; R41; L96; 330; value of information; information flow; willingness to pay; value of time; face-to-face communication; telecommunication information input–output table; head office; branch offices Firm behaviour; Spatial economic model